Current trends in gene-enhanced tissue engineering for articular cartilage regeneration in animal model - Mohamed Amin, Muhammad Azri Ifwat; Azhim, Azran; Mohamed Sideek, Mohamed Arshad; Zulkifly, Ahmad Hafiz; Sha'ban, Munirah (Persatuan Genetik Malaysia (Genetics Society of Malaysia), 2017)
The aim of this review was to summarize and discuss the patterns and trends of the combination of cartilage tissue engineering and gene transfer approaches in in vivo preclinical (or, animal) studies. Electronic literature search of articles published in the Web of Science (WOS) and SCOPUS databases was done based on the following keywords: “tissue engineering”, “articular cartilage”, “animal OR vivo” and “gene”. Two levels of screening were used i.e. based on selected themes and full-text availability of the articles. Inclusion criteria were original full-text papers of preclinical studies using tissue engineering application and gene transfer strategy for articular cartilage regeneration. While, exclusion criteria were conference and review papers, and drug delivery based studies. The search yielded a total of 632 articles (WOS=211; SCOPUS=421). Out of 632, only 612 articles were selected after the removal of 20 overlapping articles from both WOS and SCOPUS databases. After further screening had completed, only 35 articles were included based on their relevancy to this study. Eight (8) articles were then excluded because full-text version of publications was not available. With that, only 27 articles left and included in this present review. The trend in animal studies shows the use of TGF-β (33.33%) and SOX9 (14.81%) transfections enhance chondrogenic differentiation, whilst TGF-β and ChM-1 (3.70%) maintain the chondrocytic phenotype. The co-transfection of TGF-β and BMP (40.74%) promote the integration between tissue engineered implant and the adjacent host cartilage in animal models. Other genes such as IGF-1 (7.41%), CTGF (3.70%) and Bcl-Xl (3.70%) have been reported to enhance cartilage regeneration. In conclusion, the use of genes transfer approach for cartilage tissue engineering in various animal models promotes articular cartilage regeneration which may be useful for future clinical setting.